Live secondary abdominal pregnancy- by chance!! - Sood, Akanksha; Katke, R. D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Abdominal pregnancy though rare but is a life threatening situation, if not recognized and managed properly. We are hereby presenting a rare successful outcome in a case of ruptured live Secondary Abdominal pregnancy with placental implants over intestines.